Evaluation of Taman Lansia Based on Recreational Needs and Functions According to Elderly Perceptions - TB. Muhammad Naufal Rabbani; Tia Adelia Suryani (Jurnal Planologi, 2023)
Bandung City  is one of the cities in Indonesia where the percentage of the growth of the elderly community is quite high, so it is necessary to provide special recreational and sports facilities for the elderly community. The park was chosen as a place of recreation because it is considered to be able to refresh physically and psychologically. Many elderly people experience difficulties and feel uncomfortable when doing activities in the park because there is no special development of parks for the elderly from the government. This study aims to analyze the use of green open space from the recreational function and its needs based on the perception of the elderly. The method used is descriptive quantitative based on data obtained from the results of distributing questionnaires and field observations using accidental sampling of visitors. Based on the results of the study, the characteristics of visitors were dominated by men with an age range of 60-64 years and still living with a partner and still earning. The existing condition of the park is in quite good condition. The majority of elderly activities in the park are leisurely walks, while the most comfortable recreational activity to do is relax. The needs of the elderly for parks are dominant in physical needs such as more for park public facilities. There are 3 (three) factors that shape the motivation to visit the elderly at Taman Lansia. Factor 1 consists of location security, convenience of street vendors, and convenience of trash cans. Factor 2 is location accessibility and signage convenience. While factor 3 includes route accessibility, crowd safety, pedestrian path comfort, and toilet comfort.Keywords: perception, recreation, green open space, Taman Lansia